Comparison Study of Three Industrial Parks in Central Java Indonesia - Sujarwanto Dwiatmoko; Sri Suwitri; Hardi Warsono; Ida Hayu Dwimawanti; Alfina Handayani (The Indonesian Journal of Planning and Development, 2018)
Compared with other Industrial parks in Jababeka, West and East Java, industrial parks progress in Central Java are less developed. This condition is mainly due to the lack of optimal management. Only limited studies comprehensively discuss the differences among in industrial parks in Central Java in particularly in management aspect. The research aims to comparatively analyze the differences and similarities of three industrial parks in term of their administration (location selection and preparation), infrastructure provision and management. This research adopts a descriptive-qualitative research method to discuss a particular research problem. The previous survey of this study was conducted in eight industrial parks management in Central Java. Three industrial parks (KIW, Terboyo, and BSB) representing industrial park s as a core business, an industrial plot provider and a residential area supporter were profoundly explored in dept. The data were collected through observation, focus group discussion (FGD), in-depth interviews and documentation. The key informants are the industrial park manager s and their team. The result s show that jurisdictional prerequisites are an important factor in the development of industrial estates, affecting construction costs and future management. The provision of infrastructure is fairly adequate. The quality of industrial park management does not depend on the status of ownership but the professionalism of the manager and tenant satisfaction. Both KIW and BSB have proved to offer better service performance than Terboyo. As own state regulation, however, KIW, there are many strict regulations and supervision, especially in land acquisition. Hence, the concept of land banking and supportive regulation are needed. Finally, the manager's commitment is pivotal to carry out the business and master plans.